Optimization of the operating parameters to improve the performance of peanut cake as primary coagulant for leachate pretreatment - Lida Arjmand Tajaddini (2023)
This study aims to investigate the potential of the peanut seeds as primary coagulant in the treatment of leachate, also obtaining dosage of peanut stock solution has token into account. The pH of leachate has been optimized for the coagulation by peanut cake. Moreover, optimizing the operating parameters namely rapid mixing time, slow mixing time and settling time, have been obtained.